Cultural narratives : - Jain, Jasbir (Rawat Publications, 2012)
Cultural Narratives: Hybridity & Other Spaces is a collection of essays which concern themselves with the dialogic relations between narrative and space. As they move from traditional, folk, and community narratives into hybrid spaces and urban locations, the relationship between the two - narrative and space - reflects a spatial history of the telling of the tale. Spatial concepts, such as the personal and the political, are in themselves abstractions, concretely experienced and expressed only by a living agent. The contestation between the two is of long standing with the interconnections becoming visible only in recent years. Community narratives throw up the reality of spatial divisions and bring alive relationships which are fast disappearing in an urban world. These narratives are vibrant and keep alive the values of human sympathy, compassion, and understanding, while urban narratives become fragmented, temporary, fluid, and are compartmentalized through technology and the fluidity of spaces. Together, creative writers and critics explore these overlappings as they work with experiences and histories across time and cultures and invite the reader to participate in the opening out of these spatial metaphors in the contexts of both postmodern and postcolonial constructs.